Análise das vivências de protagonismo, cooperação e interação com a comunidade através da organização de evento por alunos de ensino médio de uma escola pública de São Gabriel, Rio Grande do Sul. - Pinto, Jaqueline Miranda (2018)
The present work has as object the analysis of an differentiated curricular activity, in which high school students that completed the course, is the last year, in a public school of São Gabriel/RS, advisor by Biology teacher, act as organizing committee of an event of Science and technology dissemination, called Environmental‟s Week (SMA). To carry out the SMA, the students who are in the last year of high school, they are distributed in teams, according tasks they choose to do. Fourteen commissions are formed that, acting in a coordenated way, to allow the development of a event that takes place in three days (24 hours duration), including lectures, panel discussions, practice activities as workshops, fieldworks, cultural presentations and integration‟s social moments. The teams‟ performance is organize from a definition of coordinators, who become responsible for managing tasks that should be shared and distributed in the group.The monitoring of each group and activities integration of all teams, as well as management of diferents stages is the responsability of the teacher whosupervising the event.In 2016, the SMA has reached its fourth edition and since it started it has attracted the attention the effects of students‟ protagonism in skills acquisition that in classroom don‟t manifest themselves in a obvious way.Starting from this observation, has developed the investigation about the effects of event SMA between students and teachers, searching to register and analyze the different perceptionsabout students‟ learning and skills acquisition on activities development. Different segments were investigated: students who participated as listeners, students from organization committee, students who participated in organization of SMAfirsts editions, teachers that don‟t act in event organization, directive team, parents and speakers. Key words: Students‟